THE EFFECTIVENESS OF PEER FEEDBACK THROUGH INSTAGRAM ON TENTH-GRADE STUDENTS’ SPEAKING SKILLS IN AN EFL HIGH SCHOOL - Renita, Renita; Irawan, Rifki (ELTR Journal, 2024)
In the flow of learning objectives (ATP), students are required to master speaking skills, especially in the aspects of pronunciation, fluency, and accuracy. Students need help getting it, and one of the causes is the need for more effective learning media. This research aims to find out the effectiveness of peer feedback through Instagram on tenth-grade students' speaking skills at SMAN 1 Gamping. This research was carried out at SMAN 1 Gamping and used quantitative methods with a quasi-experimental design. Class X B is the control class that is treated with traditional peer feedback. In contrast, class X C is the experimental class that is treated with peer feedback through Instagram. The instrument used was a test (speaking skill) with the following research steps: pre-test – treatment – post-test. The hypothesis test used is the t-test with = 5% (0.05). The paired sample t-test proves that peer feedback through Instagram is effective in improving tenth-grade students' speaking skills at SMAN 1 Gamping. The independent sample proves that traditional peer feedback is superior and is more recommended for implementation.